Gestión administrativa del GAD Parroquial Antonio Sotomayor durante el periodo 2023. - Palacios Barco, Salma María (2024)
This case study refers to the Administrative Management of the Autonomous Decentralized Parish Government of Antonio Sotomayor in the period 2023. Antonio Sotomayor is a rural parish that depends on the GAD for the provision of services and community development. During the 2023 period, the parish noted significant problems that affected its work and the quality of life of its citizens, the main problems were poor administration, lack of resources and labor inefficiency. The GAD management was clear in the lack of strategic planning, ineffective decisions and poor communication between its areas. The parish suffered from chronic insufficiency in financial and material resources. This is due to a combination of limited budgets, lack of investment and ineffective tax collection. There was a notable lack of motivation and training among GAD employees. Excessive bureaucracy and lack of procedures contributed to reduced productivity and unfavorable service to the community. With more efficient administration, optimization of available resources and an increase in work efficiency, it is possible to transform.